OPTIMALISASI WAKAF DALAM SEKTOR PENDIDIKAN - Maharani, Sindi Aurora; Putra, Purnama; Sara, Dem Vi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
The understanding of traditional communities about waqf is very limited, traditional paradigm only know that waqf is only in the form of fixed assets such as land and buildings. Over time cash waqf emerged. But there are still many traditional paradigm who do not know and disagree about cash waqf. Education is a very important factor to create the character of a nation. Educational Waqf is an important instrument in the development of Islamic community education. Therefore, waqf is needed for the Islamic education sector. This research seek disclosure how the management of waqf for education in Indonesia and Malaysia is able to present a perspective and model that can be used as a reference for the management of waqf in optimalizing education sector using comparative descriptive methods. The results of this study are optimization of the education sector waqf by making professional waqf management institutions, optimizing existing assets by involving stakeholders and requiring the role of government in the collection and management of waqf.